Deskripce a reference - Koťátko, Petr (Organon F, 1997)
The first part pleads for the Fregean account of definite descriptions as expressions referring to the objects which satisfy them. In particular, it attempts to give a clear sense to the idea of a descriptionś referentially contributing to the truth conditions of the complete utterance, even if the Russellian specification of truth-conditions is accepted. The second part examines a special case in which a description (like in Donnellanś referential use) can be thought of as referring to an object which does not satisfy it. This leads to the general question of the role of agreement between the speakerś and the audienceś beliefs in the determination of reference and utterance meaning. The question is discussed from the point of view of the Davidsonian account of utterance meaning as constituted by the match between speakerś actual communicative intentions and audienceś hypotheses about these intentions. The third part provides arguments in favour of an alternative account of utterance meaning as a set of the normative consequences of the utterance and shows that a corresponding question makes sense even there.